Neutral bremsstrahlung electroluminescence in noble liquids. (1st January 2022) - Borisova, E.; Buzulutskov, A.
Abstract: Proportional electroluminescence (EL) is the physical effect used in two-phase dark matter detectors, to optically record in the gas phase the ionization signal produced by particle scattering in the liquid phase. In our previous works the presence of a new EL mechanism in noble gases, namely that of neutral bremsstrahlung (NBrS), was demonstrated both theoretically and experimentally, in addition to the ordinary EL mechanism due to excimer emission. In this work we show that the similar theoretical approach can apply to noble liquids, namely to liquid helium, neon, argon, krypton and xenon. In particular, the photon yields and spectra for NBrS EL in noble liquids have been calculated for the first time, using the electron energy and transport parameters obtained in the framework of Cohen-Lekner and Atrazhev theory. The relevance of the results obtained to the development of noble liquid detectors for dark matter searches and neutrino experiments is discussed.